YOUTH, TALENT AND PASSION FOR BULGARIAN FOLK MUSIC - Petrova-Kirkova, Galya (E-Journal VFU, 2025)
The present text is an evaluation/analysis of the artistic, concert and recording activities of the "Royal Band" orchestra led by Stefan Yordanov, in particular the presentation of the creative team at the festival of wedding music - Stambolovo, 2024.